Ethical Challenges and Opportunities of Nutritional Interventions Study In Night Shift Worker - Harun, Hasniah; Wagiu Basrowi, Ray (Ridwan Institute, 2024)
Nutritional intervention research among night shift workers has gained significant attention due to the rising concerns about poor overeating habits in this population. While such studies hold promise for improving health outcomes, they also raise important ethical issues that must be carefully considered. We conducted via the electronic database, Google Scholar. We selected 3 articles from the past 5 years, using the keywords: ethics, nutritional intervention, night shift worker. Articles that do not meet the keywords will be excluded from the review. Total of 3 articles as literature review. these research has a similarity, participants are prohibited from eating between 1 am 6 am. The ethical issues that may arise in these three research are respect for persons (autonomy) and beneficence (non-maleficence). Currently, nutritional interventions among night shift workers commonly involve implementing a five-hour nightly fast. The ethical issues that may arise in this research include respect for persons (autonomy) and beneficence (non-maleficence). As new studies emerge, interventions involving specific nutrients or dietary restrictions, such as carbohydrate/fat intake limitations during night shifts, may present new ethical challenges.